2017
DOI: 10.1007/s11427-016-0369-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic small molecule YF-452 inhibits tumor growth through antiangiogenesis by suppressing VEGF receptor 2 signaling

Abstract: Tumor angiogenesis is characterized by abnormal vessel morphology, endowing tumor with highly hypoxia and unresponsive toward treatment. To date, mounting angiogenic factors have been discovered as therapeutic targets in antiangiogenic drug development. Among them, vascular endothelial growth factor receptor 2 (VEGFR2) inhibitors exerts potent antiangiogenic activity in tumor therapy. Therefore, it may provide a valid strategy for cancer treatment through targeting the tumor angiogenesis via VEGFR2 pathway. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“… 33 Downregulation of VEGF could inhibit cell proliferation and lead to tumor cell apoptosis. 34 In our study, we found that MAGEC2 could enhance the expression and secretion of VEGF, and silencing MAGEC2 could significantly suppress the expression of VEGF and the progression of angiogenesis, indicating that MAGEC2 could positively regulate VEGF activation and it might be a potential target for antiangiogenesis therapy.…”
Section: Discussionmentioning
confidence: 53%
“… 33 Downregulation of VEGF could inhibit cell proliferation and lead to tumor cell apoptosis. 34 In our study, we found that MAGEC2 could enhance the expression and secretion of VEGF, and silencing MAGEC2 could significantly suppress the expression of VEGF and the progression of angiogenesis, indicating that MAGEC2 could positively regulate VEGF activation and it might be a potential target for antiangiogenesis therapy.…”
Section: Discussionmentioning
confidence: 53%
“…It is well recognized that the cancer cell viability is assumed generally evaluated by CCK8 assay [ 5 , 39 , 40 , 41 , 42 ]. In this study, the IC 50 was used to preliminarily evaluate the PPO’s anti-proliferative effect of breast, ovarian, prostate, and lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, with an increasing number of patients with cancer in social, economic, and electronic technology, the upward trend is becoming more and more severe [ 1 ]. There are many studies on the treatment of cancer, for example, some synthetics and their derivatives can play an anti-tumor effect on breast cancer [ 2 , 3 ]; at the same time, the synthesis of small molecules [ 4 , 5 , 6 ], cell targeting [ 7 ] and drug targeting [ 8 ] have also become novel paths for the treatment of breast cancer. Androgen deprivation therapy, targeted androgen therapy, immunotherapy, and other treatment methods [ 9 , 10 , 11 , 12 ] are currently the most effective treatment for prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A chemogenomic library is a relatively small library containing hundreds-to-thousands (rather than millions) of selective small molecules with known or potential targets or functions, of which the majority target G protein-coupled receptors, kinases and ion channels, the most common molecular targets for drug discovery [ 22 ]. Using such a library can greatly increase the opportunity to repurpose a drug that acts on a novel pathway or target [ 23 ]. It should be pointed out that dark chemical matter, those small molecules in a screening collection that have never shown biological activity despite having been exhaustively tested in high-throughput screening, has also been reported to occasionally result in potent hits with unique activity and clean safety profiles, which makes them valuable starting points for lead optimization efforts [ 7 , 24 ].…”
Section: Chemical Librarymentioning
confidence: 99%